The determining factors of COVID-19 vaccination uptake among elderly in Indonesia - Intan Putri; Hari Purnomo (International Journal of Public Health Science (IJPHS), 2022)
The elderly is the most vulnerable population group during COVID-19 pandemic. Unfortunately, the vaccination uptake against COVID-19 among the seniors was considered low. This research aimed to point out the most significant factor as the recommendation for government to develop strategy in increasing COVID-19 participation among elderly. The variables are the health belief model, trust in health authorities and media, the experience regarding COVID-19, the general vaccination behaviour, and the novel contribution is the addition of the health protocol compliance as the determining factors of Covid-19 vaccination uptake action among the elderly in Indonesia. The online survey using a structured questionnaire obtained 213 respondents aged ≥55 years old. Structured Equation Modelling was employed to test the model. The result showed that the health belief model (β=0.296), trust in media and authorities (β=0.524), and general vaccination behaviour (β=0.319) significantly affect health protocol compliance. The health belief model (β=0.699), trust in media authorities (β=0.933), and health protocol compliance (β=0.406) significantly affected the COVID-19 vaccination uptake behaviour. This result gives the implication that the government should focus on improving the trust in media and authorities among the elderly. This action would improve the knowledge of COVID-19 and increase the vaccination coverage among the elderly.